(untitled) (Baghdad Science Journal, 2011)
The work in this paper focuses on the system quality of direct and coherent communication system for two computers. A system quality is represented by Signal to Noise ratio (SNR) and Bit Error Rate (BER). First part of the work includes implementation of direct optical fiber communication system and measure the system quality .The second part of the work include implementation both the( homodyne and heterodyne)coherent optical fiber communication system and measure the system quality . Laser diode 1310 nm wavelength with its drive circuit used in the transmitter circuit . A single mode of 62.11 km optical fiber is selected as transmission medium . A PIN photo detector is used in the receiver circuit. The optical D-coupler was used to combine the optical signal that come from transmitter laser source with optical signal of laser local oscillator at 1310/1550 nm to obtain coherent detection . Results show that for direct detection the SNR and the BER (28.5 dB, 9.64x10-8,) respectively, while for homodyne and heterodyne coherent detection , the SNR(94.36,97.71)dB and the BER are (1.32x10-22,2.43x10-23) at maximum optical fiber length at 62.11 km. Results show that the homodyne and heterodyne detection are better than direct detection because the large output SNR and low BER of the received signal.